2008
DOI: 10.1007/s10646-008-0259-0
|View full text |Cite
|
Sign up to set email alerts
|

Genotoxic effects of produced waters in mosquito fish (Gambusia affinis)

Abstract: The aim of this study was to assess the potential genotoxic effects of produced water (PW) from an Italian on-shore oil plant. Produced water is a complex mixture containing residual hydrocarbons, trace elements, naturally occurring radioactive material and potentially toxic treatment chemicals such as biocides, dispersants, detergents and scale inhibitors used in oil production. The test organism, mosquito fish (Gambusia affinis), was divided into male and female groups and exposed for 8 days in the laborator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 25 publications
(23 reference statements)
1
15
1
Order By: Relevance
“…The log BAF of PYOH in animals exposed to this compound was -1.7 AE 1.7, not significantly different by t-test ( p ¼ 0.4). These values, along with the high proportion of each compound that was metabolized, are consistent with values reported for other benthic invertebrates able to biotransform PAH effectively [40]. Another species of whelk, N. lyrata, exposed to PYOH through spiked food at lower levels, also exhibited a mean log BAF of -1.7 [28].…”
Section: Bioaccumulation and Biotransformationsupporting
confidence: 86%
See 1 more Smart Citation
“…The log BAF of PYOH in animals exposed to this compound was -1.7 AE 1.7, not significantly different by t-test ( p ¼ 0.4). These values, along with the high proportion of each compound that was metabolized, are consistent with values reported for other benthic invertebrates able to biotransform PAH effectively [40]. Another species of whelk, N. lyrata, exposed to PYOH through spiked food at lower levels, also exhibited a mean log BAF of -1.7 [28].…”
Section: Bioaccumulation and Biotransformationsupporting
confidence: 86%
“…In previous studies, differences have been noted between PAH metabolites as well as corresponding toxic effects detected in different sexes of fish [40]. In the present study, such differences could have been obscured by variability in the feeding of the whelks.…”
Section: Bioaccumulation and Biotransformationmentioning
confidence: 43%
“…In effluents of oil drilling wells onshore and in areas contaminated by pipeline leakages, PAH concentrations were similar to 100 % WSFG, being associated with induction of genotoxicity and mutagenicity (Leme and Marin-Morales 2008;Caliani et al 2009). Besides the concentration in the water column, large amounts of those compounds are found in sediments (Manoli et al 2000;Chen et al 2004), suggesting that the health of benthic organisms could be at risk due to continuous exposure to PAHs.…”
Section: Resultsmentioning
confidence: 95%
“…Fibroblast cell cultures were processed for the comet assay after Caliani et al [13], with some modifications. The cells were centrifuged at 1000 g for 10 min, then were embedded in agarose (0.5% low-melting agarose) and layered on conventional slides, predipped in 1% normal melting agarose.…”
Section: Genotoxicity Biomarker: Comet Assaymentioning
confidence: 99%
“…Others, such as polycyclic aromatic hydrocarbons (PAHs), derived from both natural (e.g., oil spills, forest fires, natural petroleum seeps) and anthropogenic (e.g., combustion of fossil fuels, use of oil for cooking and heating, coal burning) sources, are carcinogenic, teratogenic and mutagenic compounds [11] and some studies have shown that PAHs with four or more rings can induce dioxin-like activity and weak estrogenic responses [12]. Moreover PAHs have attracted scientific interest due to their genotoxicity [13]. But how is it possible to discriminate the effects of a specific toxic in a mixture of many pollutants and assess the susceptibility of a particular cetacean species to just one class of contaminants?…”
Section: Introductionmentioning
confidence: 99%